Pelaksanaan Prinsip Akuntabilitas Dalam Meningkatkan Kualitas Pelayanan Publik (Studi Pada Kantor Camat Dangia Kabupaten Kolaka Timur) - Musayyana, Musayyana; Justawan, Justawan; Manguntara, La (Universitas Halu Oleo, 2021)
The problem in this research is how the implementation of the principle of accountability in improving the quality of public services at the Dangia sub-district office in the East Kolaka Regency. The purpose to be achieved in this study is to find out the Implementation of the Principles of Accountability in Improving the Quality of Public Services at the Dangia District Head Office in East Kolaka Regency. This research was conducted at the Dangia Sub-District Head Office in East Kolaka Regency where, the Informants in this study were the heads of the Dangia Sub-District Office, the Sub-District Secretary and several Communities in Dangia Sub-District, East Kolaka Regency. Data collection techniques in this research are using interview and observation methods. The data analysis technique in this study uses primary data and secondary data, the data collected will be analyzed qualitatively. The indicators used to measure the Implementation of the Principles of Accountability in Improving the Quality of Public Services include: Legal Accountability, Performance Accountability, Program Accountability, Policy Accountability, Financial Accountability, Awareness Factors, Rule Factors, Organizational Factors, Organizational Factors, Skill Factors and Means Factors.The results of the research based on these indicators show that the Implementation of the Principles of Accountability in Improving the Quality of Public Services at the Dangia Sub-District Head Office in East Kolaka District has been well implemented, but there are still some things that need to be corrected, namely in terms of employee discipline and facilities/ infrastructure. inadequate so that it becomes a problem in the process of public service.